Analisis Pengaruh Host Country terhadap Perusahaan Multinasional: Skandal â€œDieselgateâ€ Volkswagen Group di Amerika Serikat - Ahmad, Yoga Alghazi; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Bargaining position is an important part in the dynamics of relations between actors in international relations. Bargaining position can be regarded as a connecting bridge for a party to show leverage and to reach the intended outcome or interest. In the case of the